Processes and Procedures in Self-Control: A Working Mode - Thoresen, Carl E.; Kirmil-Gray, Kathleen; Crosbie, Peggy (Canadian Journal of Counselling and Psychotherapy, 2012)
The processes of self-control involved in solving complex human problems consist of conscious effort, focused attention and choice between conflicting alternatives. Viewed as a complex set of specific teachable skills, self-control can be learned by clients and others if structured learning experiences are provided. Procedures such as identifying problems, assessing and building commitment, becoming more aware of behavior patterns, and using and evaluating action plans are presented within a social learning framework with an emphasis on reciprocal effects of cognitive, behavioraland environmental influences.